Integrasi Penelitian dan Pengabdian Kepada Masyarakat Berbasis Digital bagi Dosen STKIP Sinar Pancasila Betun - Kabupaten Malaka - Gracia Otta; Yanpitherzon Liunokas; Soleman Dapa Taka (Jurnal Kelimutu Pengabdian Masyarakat, 2022)
In this digital era, lecturers are expected to have digital-based skills that support learning activities in the classroom. Therefore, to organize cooperation as well as implement digital-based learning, Community Service activities were held for lecturers at the Sinar Pancasila Betun (STKIP) - Malaka Regency. Based on the analysis of the situation, several things that are considered priority issues that must be resolved include: (1) Alignment and integration of the Tridharma. (2) Integrating the preparation of digital-based Lesson Plans (RPS) with research and community service. (3) Implementing service into community service and vice versa. The solution provided is expected to produce the following results: In the first session, the team approached the lecturers regarding the need in teaching learning in the classroom. According to the results of the discussion is how to integrate the results of academic research with community service. Activities in the second session include lectures and discussions. While in the third session, the mentoring process is aimed at producing digital-based scientific work products.